SYNTHESIS OF AROMATIC URETHANE - CESTI PIETRO; BOSETTI ALDO; CARLETTI VITTORIO; CAUCHI EMANUELE (1999)
PROBLEM TO BE SOLVED: To obtain the subject compound in high yield and selectivity by carrying out a reaction of an organic carbonic acid ester with an aromatic amine while partially removing the alcohol formed in the reaction. SOLUTION: (A) An organic carbonic acid ester of an amount more than a stoichiometric amount is reacted with (B) an aromatic amine of formulas I to III [R is H, a halogen, a 1-8C hydrocarbyl or hydrocarbyloxy; A is a 1-6C divalent hydrocarbon; (n) is 0 or 1; (x) is 1-6] in the presence of a Lewis acid catalyst at 100-190 deg.C. In this case, the reaction is carried out while partially distilling the alcohol generated in the reaction system so that the alcohol may be maintained to 10-40 mol.% of the total amount of the alcohol to be generated. Finally, the aromatic urethane included in the reaction mixture is separated, and refined. Ethylene carbonate, styrene carbonate, dimethyl carbonate, etc., are used as the component A. The component B is preferably 4,4'- methylenedianiline, etc.